Analisis Efektivitas Pembelajaran Daring dan Prestasi Mahasiswa Akuntansi Syariah di Masa Pandemi IAIN Pekalongan - Ani Syafa'ah; Hendri Hermawan Hakim (Jurnal Pendidikan Akuntansi (JPAK), 2022)
Teaching and learning activities in all schools, which are usually carried out face-to-face, are now forced to be conducted online due to the COVID-19 pandemic. The purpose of this study was to obtain information about the effect of online learning during the pandemic on the learning effectiveness and achievement of Islamic accounting students at IAIN Pekalongan. The approach chosen is a descriptive qualitative approach. The data collection technique used in this research is to use the questionnaire method. The data collection was carried out online using a google form which was distributed to Islamic accounting students at IAIN Pekalongan class of 2020 who had carried out online learning activities with a total of 45 respondents via whatsapp media. The result of this research is that online learning greatly influences the learning effectiveness and achievement of Islamic accounting students at IAIN Pekalongan. The students still experience many obstacles, difficulties in understanding, mastering, and implementing the lecture materials they get online.